Business Development at Manba'ul Qur'an Harjowinangun Islamic Boarding School: The Barriers and Solutions - Hanifah, Khusnul; Qory'ah, Sayyidatul; Wahidmurni, Wahidmurni; Zuhroh, Ni’matuz (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2024)
Currently, Islamic boarding schools are no longer considered solely religious institutions, but have also become social entities that grow and develop. They continue to answer the problems of local communities, The purpose of this research is to find out the barriers and solutions from the development of the Manba'ul Qur'an Harjowinangun Islamic Boarding School business unit. The research method is qualitative research, case studies, and data collection techniques using observation, interview, and documentation techniques. Data analysis techniques use data condensation, data presentation, and conclusion drawn. The results of this study show that there are two business units Manba'ul Qur'an Islamic boarding school, namely Kopontren and agricultural (Rice and mung beans). The barriers in running the Cooperative business are the lack of facilities and infrastructure, lack of ability to run the cooperative system management, and student holidays. The barrier in running an agricultural business is the lack of human resources and with this barrier, a solution is found by expanding cooperation and involvement of the surrounding community as workers or additional human resources for rice field workers.